2010
DOI: 10.1097/mao.0b013e3181e8cc6d
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Dilation Eustachian Tuboplasty

Abstract: This newly introduced method seems to be a feasible and safe procedure to dilate the Eustachian tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
96
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 8 publications
2
96
0
3
Order By: Relevance
“…As a potential solution for this, eustachian tube balloon dilation (proposed as a treatment for chronic eustachian tube dysfunction) aims to ventilate and drain the middle ear by improving the physiological function of the eustachian tube. 6,10 The initial papers by Ockermann et al in 2010 5,6 and Poe et al in 2011 10,17 focused on establishing the safety of eustachian tube balloon dilation by performing both cadaveric and clinical studies. The cadaveric studies revealed no evidence of fractures to the cartilaginous or bony lumen, and no damage to the internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a potential solution for this, eustachian tube balloon dilation (proposed as a treatment for chronic eustachian tube dysfunction) aims to ventilate and drain the middle ear by improving the physiological function of the eustachian tube. 6,10 The initial papers by Ockermann et al in 2010 5,6 and Poe et al in 2011 10,17 focused on establishing the safety of eustachian tube balloon dilation by performing both cadaveric and clinical studies. The cadaveric studies revealed no evidence of fractures to the cartilaginous or bony lumen, and no damage to the internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…Only minor mucosal lacerations at the eustachian tube orifice were noted. 5,17 Since then, numerous prospective cohort studies have examined the role of eustachian tube balloon dilation. Pooled data analysis in this review revealed that the ability to perform a Valsalva improved from 8 per cent pre-eustachian tube balloon dilation to 72 per cent post-eustachian tube balloon dilation, while the rate of type A tympanograms increased from 5 to 61 per cent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Дилатация слухо-вой трубы с баллоном, введенным в хрящевую часть слу-ховой трубы под контролем эндоскопа, была предложена в 2010 г. H. Sudhoff и соавт. [7,8], которые представили доказательства ее эффективности.…”
unclassified
“…Nasal pathologies have been shown to worsen the middle ear ventilation via a negative influence on airflow parameters. Nasal obstruction has been reported to increase nasal resistance to airflow, thereby changing the opening pressure threshold of the ET [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%